1992
DOI: 10.1007/bf02814579
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbon and nitrogen sources on the production of penitrem B byPenicillium aurantiogriseum

Abstract: Effect of different carbon and nitrogen sources on the production of penitrem B was studied. D-Xylose induced maximum penitrem B production, while melibiose, glycerol, citric acid and succinic acid were poor substrates. Potassium nitrate, L-asparagine, sodium nitrate, glycine, DL-aspartic acid and L-tryptophan supported good production of penitrem B. Conversely zirconyl nitrate, barium nitrate, aluminum nitrate, acetanilide, 4-aminobenzoic acid, 4-nitrobenzoic acid and 4-nitroaniline were toxic and did not eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…For the production of penitrem B by P. aurantiogriseum , different synthetic media, supplemented with various nitrogen and carbon sources, have been examined. In this study, D-xylose was found to induce the maximum penitrem B production, whereas glycerol, citric acid and succinic acid had negative effects [ 38 ]. The same authors reported an increased penitrem B production by P. aurantiogriseum , grown on yeast extract medium, supplemented with sucrose and KNO 3 [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the production of penitrem B by P. aurantiogriseum , different synthetic media, supplemented with various nitrogen and carbon sources, have been examined. In this study, D-xylose was found to induce the maximum penitrem B production, whereas glycerol, citric acid and succinic acid had negative effects [ 38 ]. The same authors reported an increased penitrem B production by P. aurantiogriseum , grown on yeast extract medium, supplemented with sucrose and KNO 3 [ 39 ].…”
Section: Introductionmentioning
confidence: 99%